The Human Rights Implications of Not-for-Profit Surrogacy Organizations in Cross-Border Commercial Surrogacy: An Australian Case Study. Issue 1 (February 2022) - Luo, Yingyi; Marshall, Shelley; Cuthbert, Denise
Abstract : Cross-border surrogacy is a global industry that offers intended parents options for family formation by providing foreign surrogate mothers remuneration, directly or via an intermediary, in excess of their actual out-of-pocket expenses. It is a multi-million-dollar business with no international regulation. 1 In most countries, limited domestic regulation or oversight is in place. Many countries − such as Australia, the United Kingdom, New Zealand, Canada, Hong Kong and South Africa − only permit altruistic surrogacy, while Germany and France ban surrogacy entirely. 2 Fully legalized commercial surrogacy is the model followed in some states in the United States of America (USA), as well as Georgia and Ukraine. 3 This unregulated cross-border market has produced a lucrative business, with surrogacy arrangements growing by nearly 1, 000 per cent between 2006 and 2010. 4 The for-profit surrogacy sector has expanded and fertility not-for-profit organizations have also entered the market. 5